Phytoplankton size distributions in the western North Atlantic and their seasonal variability - Nils Haëntjens; Emmanuel S. Boss; Jason R. Graff; Alison P. Chase; Lee Karp‐Boss (Limnology and Oceanography, 2022)
Phytoplankton play a major role on Earth, impacting the global distribution and cycles of carbon, oxygen, nitrogen, sulfur, and other elements, and structuring marine food webs. One fundamental trait of phytoplankton with direct biogeochemical implications is their size, as it governs metabolic and sinking rates as well as prey–predator interactions. Phytoplankton size spans approximately 3.5 orders of magnitude (when expressed as an equivalent spherical diameter), and thus measuring the full range in size distribution of phytoplankton is challenging and rarely attempted. Here, we constructed phytoplankton size spectra by merging state‐of‐the‐art cytometry and imaging cytometry measurements that were collected in the western North Atlantic Ocean, along a latitudinal gradient (36°N to 55°N) and during different phases of the annual cycle of phytoplankton. The derived spectra show a seasonal pattern that parallels changes in phytoplankton biomass, and do not always follow a commonly assumed power‐law model. Shifts in size spectra were more pronounced in the sub‐Arctic and temperate subregions, compared to the subtropical region of the study area. We evaluated the relationships between different size groups and environmental parameters to derive ecologically meaningful size groups. Finally, to simulate Ocean Color remote‐sensing algorithms of phytoplankton size, we compared temporal variations in descriptors of the size spectra (median particle size, phytoplankton size distribution exponent) with optical size proxies derived from light absorption and attenuation; good agreement was observed in the northern sections of the study area where temporal changes in community size structure were more pronounced.